Surgical approaches to the superior mesenteric artery during minimally invasive pancreaticoduodenectomy: A systematic review. (18th February 2021) - Nagakawa, Yuichi; Watanabe, Yusuke; Kozono, Shingo; Boggi, Ugo; Palanivelu, Chinnusamy; Liu, Rong; Wang, Shin‐E; He, Jin; Nishino, Hitoe; Ohtsuka, Takao; Ban, Daisuke; Nakata, Kohei; et al.
Abstract: Background: Minimally invasive pancreaticoduodenectomy (MIPD) has recently been safely performed by experts, and various methods for resection have been reported. This review summarizes the literature describing surgical approaches for MIPD. Methods: A systematic literature search of PubMed (MEDLINE) was conducted for studies reporting robotic and laparoscopic pancreaticoduodenectomy; the reference lists of review articles were searched. Of 444 articles yielded, 23 manuscripts describing the surgical approach to dissect around the superior mesenteric artery (SMA), including hand‐searched articles, were assessed. Results: Various approaches to dissect around the SMA have been reported. These approaches were categorized according to the direction toward the SMA when initiating dissection around the SMA: anterior approach (two articles), posterior approach (four articles), right approach (16 articles), and left approach (three articles). Thus, many reports used the right approach. Most articles provided a technical description. Some articles showed the advantage of their method in a comparison study. However, these were single‐center retrospective studies with a small sample size. Conclusions: Various approaches for MIPD have been reported; however, few authors have reported the advantage of their methods compared to other methods. Further discussion is needed to clarify the appropriate surgical approach to the SMA during MIPD. Abstract : Highlight In this systematic review, Nagakawa and colleagues summarized the literature describing surgical approaches for minimally invasive pancreaticoduodenectomy. The approaches to dissect around the superior mesenteric artery were classified into four approaches: the anterior approach, posterior approach, right approach, and left approach. The characteristics of each approach were described using illustrations.